To solve for b in the equation x/6 - 2 = 4, we can follow these steps:
Step 1: Start by isolating the variable term on one side of the equation. In this case, we have x/6 - 2 = 4. To move the -2 to the other side, we can add 2 to both sides of the equation.
x/6 - 2 + 2 = 4 + 2
This simplifies to:
x/6 = 6
Step 2: To solve for x, we need to multiply both sides of the equation by 6 to cancel out the denominator.
6 * (x/6) = 6 * 6
The 6's on the left side cancel out, leaving us with:
x = 36
So, the value of b in the equation x/6 - 2 = 4 is 36.